2018
DOI: 10.1007/s10508-018-1176-9
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Patterns of Sexual Initiation, Sexual Partnering, and Sexual Health Outcomes from Adolescence to Early Adulthood

Abstract: The goal of this study was to examine, in a nationally representative sample, relationships between various sexual initiation patterns, subsequent sexual partnerships, and related health outcomes from adolescence through early adulthood. Data were from a subset of 6587 respondents from the National Longitudinal Study of Adolescent to Adult Health. Bivariate analyses and adjusted logistic and ordinary least squares regression models were used to determine associations between membership in three sexual initiati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
18
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 48 publications
1
18
0
1
Order By: Relevance
“…This data set is versatile in that it was used to study a variety of topics related to both adolescent and emerging adult experiences. For example, several studies used Add Health to examine dating behavior (Meier & Allen, 2009), sexual practices (Kahn & Halpern, 2018), and the role of alcohol use in later casual sex behavior during emerging adulthood (Johnson, 2013). In addition, researchers continues to use the National Longitudinal Survey of Youth 1997 (Manlove et al, 2012; https://www.nlsinfo.org/ content/cohorts/nlsy97) as well as the General Social Survey (Monto & Carey, 2014).…”
Section: Methodological Approachesmentioning
confidence: 99%
“…This data set is versatile in that it was used to study a variety of topics related to both adolescent and emerging adult experiences. For example, several studies used Add Health to examine dating behavior (Meier & Allen, 2009), sexual practices (Kahn & Halpern, 2018), and the role of alcohol use in later casual sex behavior during emerging adulthood (Johnson, 2013). In addition, researchers continues to use the National Longitudinal Survey of Youth 1997 (Manlove et al, 2012; https://www.nlsinfo.org/ content/cohorts/nlsy97) as well as the General Social Survey (Monto & Carey, 2014).…”
Section: Methodological Approachesmentioning
confidence: 99%
“…, which are both associated with higher risk for sexually transmitted infections (STIs) (Kahn & Halpern, 2018;Pflieger, Cook, Niccolai, & Connell, 2013;Van Wagoner, Harbison, Drewry, Turnipseed, & Hook, 2011). One factor that may link risky behaviors such as disordered eating and risky sex is the personality trait of impulsivity (Culbert & Klump, 2005;Liang & Tseng, 2011).…”
Section: Frommementioning
confidence: 99%
“…There is increasing evidence that risky health behaviors, which can include disordered eating, substance use, and sexual risk behaviors, tend to cluster together (Hingson & Zha, ; Mewton et al, ). Sexual risk behaviors that may cluster together include the number of sexual partners and unprotected sex (Ashenhurst, Wilhite, Harden, & Fromme, ), which are both associated with higher risk for sexually transmitted infections (STIs) (Kahn & Halpern, ; Pflieger, Cook, Niccolai, & Connell, ; Van Wagoner, Harbison, Drewry, Turnipseed, & Hook, ). One factor that may link risky behaviors such as disordered eating and risky sex is the personality trait of impulsivity (Culbert & Klump, ; Liang & Tseng, ).…”
Section: Introductionmentioning
confidence: 99%
“…In our study, the onset of sexual activity was not assessed out of concerns that in a multisite trial, the investigators could not assure patient confidentiality relative to their parents/caregivers for all participants. However, obtaining this information in future studies would be helpful in assessing clinical risk and outcomes in patients with chronic diseases (33,34). In children with CKD and on dialysis, contrary to what was believed in the past, recent cohort studies have shown that growth and sexual maturation are only slightly delayed compared to healthy subjects (35).…”
Section: Discussionmentioning
confidence: 99%